A randomized non-inferiority clinical study to assess post-exposure prophylaxis by a new purified vero cell rabies vaccine (Rabivax-S) administered by intramuscular and intradermal routes. Issue 40 (14th September 2016) - Bose, Anuradha; Munshi, Renuka; Tripathy, Radha Madhab; Madhusudana, Shampur N.; Harish, B.R.; Thaker, Saket; Mahendra, B.J.; Gunale, Bhagwat; Gogtay, Nithya J.; Thatte, Urmila M.; Mani, Reeta Subramaniam; Manjunath, K.; et al.
Abstract: Background: Rabies is a 100% fatal disease but preventable with vaccines and immunoglobulins. We have developed a new purified vero cell rabies vaccine (Rabivax-S) and evaluated its safety and immunogenicity in post-exposure prophylaxis by intramuscular (IM) and intradermal (ID) routes. Methods: This was a randomized active-controlled non-inferiority study in 180 individuals (age 5 years and above) with suspected rabies exposure (90 each with WHO Category II and Category III exposures). The participants received either Rabivax-S (1 mL IM; five doses), Rabivax-S (0.1 mL ID; eight doses) or purified chick embryo cell vaccine (PCEC, Rabipur®) (1 mL IM; five doses). The IM doses were given on Day 0, 3, 7, 14 and 28 while the ID doses were given on days 0, 3, 7 and 28. Category III patients also received a human rabies immunoglobulin (HRIG) on Day 0. Adverse events (AEs) were recorded with diary cards till day 42. Rabies neutralizing antibody levels were measured on day 0, 7, 14, 28 and 42. Results: In both the category II and III patients, the geometric mean concentration (GMC) ratios of Rabivax-S IM and Rabivax-S ID groups to PCEC IM were more than 1, thus proving the non-inferiority. GMCs were similar or higher in Rabivax-S groups at all the time points. Seroresponse against rabies (RFFIT titre ⩾ 0.5 IU/mL) was achieved in all participants. Mostly mild local and systemic adverse events were reported across the three groups and all resolved without sequelae. Conclusions: Rabivax-S was well tolerated and showed immunogenicity comparable to a licensed rabies vaccine by both IM and ID routes in post-exposure prophylaxis. Registry No.:CTRI/2012/11/003135